2016
DOI: 10.1097/id.0000000000000438
|View full text |Cite
|
Sign up to set email alerts
|

Classification of the Root Position of the Maxillary Central Incisors and its Clinical Significance in Immediate Implant Placement

Abstract: In Chinese adults, the predominant type of sagittal root position of the maxillary central incisor is buccal. This classification system is useful in planning the implant site for immediate placement in the maxillary esthetic zone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
47
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(51 citation statements)
references
References 17 publications
4
47
0
Order By: Relevance
“…Several studies have investigated the root position of the maxillary central incisors in the alveolar bone and have reported that the buccal type was the predominant incisor root position. 2 5 14 15 16 In our study, the buccal type of root position was identified in more than 90% of cases and the palatal type was found in only 2 cases (5%) of the lateral incisors, similar to the results of previous reports. 5 14 16 …”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Several studies have investigated the root position of the maxillary central incisors in the alveolar bone and have reported that the buccal type was the predominant incisor root position. 2 5 14 15 16 In our study, the buccal type of root position was identified in more than 90% of cases and the palatal type was found in only 2 cases (5%) of the lateral incisors, similar to the results of previous reports. 5 14 16 …”
Section: Discussionsupporting
confidence: 91%
“…During immediate placement, the direction of placement more or less coincided with the long axis of the tooth. 14 17 In our study, buccal subtype I accounted for 64.3% of the central incisors and 8.0% of the lateral incisors. The buccal subtype II incisors had a thinner buccal bone wall than buccal subtype I, and immediate placement was more challenging than in patients with subtype I in such cases.…”
Section: Discussionmentioning
confidence: 50%
See 2 more Smart Citations
“…This risk dramatically increases through the combination of immediate implant placement, flapless surgeries, and limited clinical experience. In these cases, the shape of the socket, and the change in resistance between the buccal and the palatal bone, may substantially influence accurate implant positioning . Recession of the facial mucosal margin was a common observation in several studies with immediate implant placement .…”
Section: Soft Tissue Complications Deriving From Improper Placement Omentioning
confidence: 99%